User-Generated Content as A Moderating Variable of the Influence of Brand Trust on Purchasing Decisions - Sumarwanto; Sulistyo Budi Utomo; Rahmat Aji Nur Yakin; Sherly Ernawaty Susanto; Eva Desembrianita (Jurnal Teknologi dan Manajemen Industri Terapan, 2025)
The primary data used in this research were obtained directly from Bank Malaysia employees across Indonesia. The data obtained was analyzed using the smart PLS 4.0 analysis tool. The results of the first row of the third table show that the Brand Trust variable can have a positive relationship direction and a significant influence on Purchasing Decisions because the P-Values ​​are positive and below the significance level of 0.05, namely 0.005. These results indicate that the Brand Trust variable can widen market share, increase sales quantity, and ultimately influence Purchasing Decisions. In addition, the User Generated Content variable can also moderate the influence of the Brand Trust variable on the Purchase Decision variable because the same thing is that the P-Values ​​value is positive and is below the significance level of 0.05, namely 0.000. After all, the  ​​P-value is positive and below the significance level of 0.05, 0.000. Thus, it can be concluded that this article's first and second hypotheses can be accepted and proven.